FRACTIONATION OF IRON (Fe) AND MANGANESE (Mn) IN THE HORIZONS OF A FOREST SOILS, AGROFORESTRY, AND DRYLAND AGRICULTURE - Parjono, Parjono; Anwar, Syaiful; Murtilaksono, Kukuh; Indriyati, Lilik (Journal of Environmental Science and Sustainable Development, 2019)
One of the main problems with acidic soils is the availability of soil nutrients. In such soils, iron (Fe) and manganese (Mn) ions are highly present. This study evaluated the Fe and Mn fractions in the soil profiles of forests used for agroforestry and dryland agriculture in the upper Ciliwung watershed. The watershed is a zone of high rainfall washing. The evaluation was based on the results of analysis of soil samples taken at four soil horizons (Ao or Ap, A1 or A2, B1, and B2) for each type of land use. Research was conducted by survey and laboratory analysis. Fractionation of Fe and Mn employed sequential extraction methods with different compounds in each fraction. Fractionation was divided into exchangeable fractions (Exch), acid extractable (Acex), can be reduced (Red), oxidized (Oxs), and residual (Res). Results showed that Res Fe was (>23000.8 ppm or 76.3%) and Oxs Mn (>1642.9 ppm or 52.9%) dominated each type of land use, while the lowest fractions were Exch Fe (<12.2 ppm or 0.022%) and Exch Mn fraction (<97.2 ppm or 1.50%) in each type of land use.